Corrosion rate measurement of coated and uncoated steel by tafel extrapolation method - Wong, Mun Foo, 1986-, author; Esah Hamzah, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2011